2021
DOI: 10.1038/s41467-021-23260-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct place cell dynamics in CA1 and CA3 encode experience in new environments

Abstract: When exploring new environments animals form spatial memories that are updated with experience and retrieved upon re-exposure to the same environment. The hippocampus is thought to support these memory processes, but how this is achieved by different subnetworks such as CA1 and CA3 remains unclear. To understand how hippocampal spatial representations emerge and evolve during familiarization, we performed 2-photon calcium imaging in mice running in new virtual environments and compared the trial-to-trial dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 73 publications
17
123
0
Order By: Relevance
“…Finally, we trained separate linear decoders to predict the normalized velocity of the mice from the binary Ca +2 activity traces, and found that their performance was not significantly different from when trained on shuffled data (mean error size: 0.2±0.02 for real traces, 0.2±0.02 for shuffled data; permutation tests, p>0.4 for all 3 mice)(Figure 4I-L), indicating that velocity cannot be decoded from the astrocytic activity. Taken together, our findings demonstrate that reconstruction of mice location trajectories from astrocytic activity can be done accurately using linear decoders, but requires familiarization with the environment, and, as opposed to neurons 36 , cannot be done in a novel environment.…”
Section: Mouse Location Can Be Decoded From Astrocytic Activitymentioning
confidence: 74%
“…Finally, we trained separate linear decoders to predict the normalized velocity of the mice from the binary Ca +2 activity traces, and found that their performance was not significantly different from when trained on shuffled data (mean error size: 0.2±0.02 for real traces, 0.2±0.02 for shuffled data; permutation tests, p>0.4 for all 3 mice)(Figure 4I-L), indicating that velocity cannot be decoded from the astrocytic activity. Taken together, our findings demonstrate that reconstruction of mice location trajectories from astrocytic activity can be done accurately using linear decoders, but requires familiarization with the environment, and, as opposed to neurons 36 , cannot be done in a novel environment.…”
Section: Mouse Location Can Be Decoded From Astrocytic Activitymentioning
confidence: 74%
“…What could be the behavioural relevance of the sensitivity of SR synapses to prior activity in either SR or SO afferents? SR inputs arise mainly although not exclusively from proximal CA3, where auto-associative connections mediate pattern completion and memory storage that is passed to area CA1 to consolidate activity there, such as place cell activity 47 . The output connections of CA1 with subicular and cortical regions are important for the replay of this information through the hippocampal and cortical circuitry and retrieval during memory retention trials as triggered by output from CA3 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FPA uhf feature can potentially overcome the issues of gradually degraded unit loss during chronic electrophysiological recordings. The degraded decoding accuracy based on LFP phase or amplitude information ( Figure 4B ) might be due to the drift of electrodes due to brain movement, or due to gradual remapping and slow drift of hippocampal representation ( Frank et al, 2004 ; Dong et al, 2021 ; Rule et al, 2019 ). In another independent investigation ( Tu et al, 2020 ), we applied the OLE decoding method to decode a rodent’s position based on calcium-imaging recordings, and demonstrated that population decoding accuracy degraded across days even when a large number (>500) of CA1 units were used.…”
Section: Discussionmentioning
confidence: 99%